A creative approach to the creation of didactic support (Texas Journal of Philology, Culture and History, 2023)
In the processes of globalization and integration of education in the world, the issue of developing the professional training of future specialists is defined as one of the urgent tasks. To increase the quality level of personnel training in Uzbekistan, to create the necessary conditions for the training of qualified specialists based on international standards, to introduce advanced pedagogical technologies, educational programs and issues of wide introduction of teaching and methodical materials, development of modern professional knowledge and creative abilities of students, scientific-pedagogical personnel were defined as the main tasks of quality improvement and fundamental improvement of the level of higher education in accordance with the priorities of the action strategy.